ANALISIS KEPUTUSAN PEMBELIAN MEUBEL DI UD. TUNGGAL JAYA BOJONEGORO - widiyanto, ibnu; sutopo, sutopo; paraswati, yunita andri (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2014)
Research on the decision to purchase a product has a lot to do. This study aims to analyze factors that influence to the buying decisions of furniture products in UD. Tunggal Jaya Bojonegoro. The factors used are product quality, distinctiveness furniture, perceptions of price, and service quality.The analytical method used to analyze the influence of the variable product quality, distinctivenessfurniture, perceptions of price, quality and services to the purchasing decision is the methodof multiple linear regression with the help of statistical program SPSS for Windows version17.0 and test hypotheses based on the p value<0, 05. The results showed that the regressionequation is formed KPKB=0.235+0.147+0.376KMPH+0.359KL.Product quality variables simultaneously (KP), the peculiarities of furniture (KM), perceivedprice (PH), and quality of service(TOS) can influence the purchase decision (KB) F-test forcoefficient values calculated at 18.718, and partially the four independent variables caninfluence purchasing decisions.Suggestions obtained researc his the needfor marketers to increase providing timely serviceat the time oft he delivery process and the existence of clear guarantees for damage product.Offer arelatively cheap price according to what promises to management of the productsoffered, giving discounts in order to attract customers to decide onthe purchase, establishquality products that comply with the promised cover form, wood quality and smooth finishing,carving and creating accessories detail the concept and create alot of variation plitur.